The Impact of Age on Electrocardiographic Findings of Stroke Patients: A Cross-Sectional Analytic Study - Osarenkhoe, Osaretin John; Alugba, Gabriel; Aiwuyo , Henry Osarume; Kweki , Anthony; Oluwasegun, Akinti; Torere, Beatrice; Oluwaseye, Oladimeji; Ugoeze , Iloeje; Obiebi , Irikefe; Ovwasa , Henry; et al. (International Journal of Health Sciences, 2023)
Purpose: To evaluate differences in ECG abnormalities in stroke patients in relation to age groups (less than forty, forty to sixty-five and greater than sixty-five years) in the University of Benin Teaching Hospital (UBTH) Methodology: This was a cross-sectional analytical study carried out at the University of Benin Teaching Hospital (UBTH), Benin. The study subjects consisted of consecutive one hundred and twenty admitted stroke patients who met the inclusion criteria. History and physical examination were carried out for all patients with laboratory investigations and electrocardiographic examinations also performed on all patients. The data was analyzed using SPSS version 21 software with a P-value of less than 0.05 considered significant for all comparisons. Result: In this study, stroke was more in those under sixty-five years (n = 84, 70.00%) than in those above sixty-five years (n = 36, 30.00%). All (100.00%), 56 (77.78%) and 24 (66.67%) of cases less than forty, forty to sixty-five years and greater than sixty-five years respectively in this study had ECG abnormalities, this was significant (p = 0.021). Unique Contribution to Theory, Policy and Practice: Left ventricular hypertrophy predominates in less than forty years old cases while left axis deviation predominates in older than forty years cases. Some ECG abnormalities in certain age groups